Distance education in the Kingdom of Saudi Arabia and the United States of America: A comparative study - Al Futaih, Hadi Hamad (Journal of Educational and Psychological Sciences, 2021)
This paper aims to shed light on distance education in the United States of America and compares it to distance education in the Kingdom of Saudi Arabia, in order to benefit from it in improving the processes of education and distance learning and how to overcome the problems facing distance education in the Kingdom of Saudi Arabia. The study used the comparative method. Among the most important findings of the study: Distance education centers contribute to literacy and educating the elderly, providing individual and varied educational resources, ensuring freedom to choose, saving time and money, the distance education system allows choosing the most appropriate time for students, self- discipline, and developing students ’intellectual skills. Among the most important recommendations of the study: Paying attention to increasing distance education centers to work on raising the cultural, scientific and social level among members of society, the necessity of using different types of distance education (simultaneous and asynchronous education), working to provide a safe environment and better communication among all students, working to provide a new world of opportunities for distance education students, and working to provide educational outcomes for those who missed learning opportunities from members of the community.